2014
DOI: 10.1002/2327-6924.12112
|View full text |Cite
|
Sign up to set email alerts
|

Childhood lead poisoning and the new Centers for Disease Control and Prevention guidelines for lead exposure

Abstract: Purpose This article will give a brief history, review the latest guidelines, discuss risk factors and sources, and discuss screening, diagnosis, and management of lead poisoning in children. Additionally, the role of the nurse practitioner (NP) caring for children will be reviewed. Data sources Review of published literature on lead poisoning and the 2012 lead prevention guidelines of the Advisory Committee on Childhood Lead Poisoning Prevention (ACCLPP) of the Centers for Disease Control and Prevention (CDC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 15 publications
0
36
0
Order By: Relevance
“…Studies have shown that no level of lead is considered safe, and the emphasis has shifted to primary prevention of lead exposure. Despite the focus on primary preventiv (Schnur et al, 2014). Lead is highly toxic to children, causing intellectual and behavioral deficits, hyperactivity, fine motor function deficits, decreased intelligence quotient, alteration of handeye coordination, and problems in reaction time.…”
Section: Effects On Humansmentioning
confidence: 99%
“…Studies have shown that no level of lead is considered safe, and the emphasis has shifted to primary prevention of lead exposure. Despite the focus on primary preventiv (Schnur et al, 2014). Lead is highly toxic to children, causing intellectual and behavioral deficits, hyperactivity, fine motor function deficits, decreased intelligence quotient, alteration of handeye coordination, and problems in reaction time.…”
Section: Effects On Humansmentioning
confidence: 99%
“…25 At the same time, with reference to the level of 'lead toxicity' in children, ACCLPP eliminated the term 'level of concern' for blood lead level (previously defined as 10 μg/dL) and replaced it with a reference level of 5 μg/dL, based on the 97.5th percentile of the population blood lead level in children aged between 1 and 5 years. 2,13,24 This was supported by the American Academy of Pediatrics who acknowledged that even the lowest degree of lead exposure might harm children, 13,23,26 and echoed the European Food Safety Authority who concluded that there is no known safe exposure to lead as evidenced by international studies in Europe. [27][28][29] In other words, there is no safe or 'non-toxic' blood lead level.…”
Section: Potential Public Health Implicationsmentioning
confidence: 99%
“…21,22 According to the latest guideline in 2012 from the Centers for Disease Control and Prevention (CDC)'s Advisory Committee on Childhood Lead Poisoning Prevention (ACCLPP), clinicians should perform an environmental assessment before screening children for lead poisoning. 13,23 This changed the practice of universal screening of all children for elevated blood lead levels 2,23,24 to targeted screening after mathematical simulations suggested that such screening among 1-year-old children may not be cost-effective, especially in communities with a lower prevalence of lead poisoning. 25 At the same time, with reference to the level of 'lead toxicity' in children, ACCLPP eliminated the term 'level of concern' for blood lead level (previously defined as 10 μg/dL) and replaced it with a reference level of 5 μg/dL, based on the 97.5th percentile of the population blood lead level in children aged between 1 and 5 years.…”
Section: Potential Public Health Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ingestion of lead paint and dust has been estimated to account for 70 % cases with elevated blood lead levels (BLLs) (Levin et al 2008;Warniment et al 2010). Dust particles that are composed of soil, paints, and industrial or automotive emissions are absorbed more easily in comparison to soil into the gastrointestinal tract of children (Schnur and John 2014). An updated list of the major sources of exposure to lead is shown in Fig.…”
Section: Leadmentioning
confidence: 99%